A Comparative Study of Water Quality Characteristics at East Java River - Sri Wahyuningsih; Nadjadji Anwar; Edijatno Edijatno; Nieke Karnaningroem (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2010)
Water is the natural resources have the function of very importance for human life and also as authorized capital in development. Water will influence by the other component. Exploiting of water to support all human life must done with wise action to management so that not result damage at water resource. As place relocation of water hence river have the selected capacities that able to change because natural activity and antropogenik. This research was conducted in nine major rivers in East Java. The objectives of this study were: 1) Identifying the characteristics and concestration range of water quality parameter, 2) Comparison the level of pollution in rivers in East Java. The results of this study indicated that the characteristic of water quality parameter of rivers in East Java were generally physical, chemical and biological. The comparison result of water quality parameter basically showed that in general the pH was still under threshold that had been determined, that was pH from 6 to 9. In general, DO concentration ranged from 0.5 mg/l to 7 mg/l, BOD concentration ranged from 3 mg/l to 11 mg/l and the COD concentration ranged between 0.5 mg/liter to 35 mg/l.